Pengaruh Financial literacy, Overconfidence dan Herding Behaviour terhadap Keputusan Investasi - Dinatonia Jovery Matruty; Lilian Sonya Loppies; Hasmia Melati Arifin (Univiversitas Dr. Djar Wattiheluw, 2024)
The study aimed to investigate the influence of financial literacy, overconfidence, and herding behavior on investment decisions in PT. Phillip Securitas Ambon Branch. It involved active investors who had invested in PT. Phillip Sekuritas Ambon Branch until 2023, with a sample size of 33 respondents. Data collection took place from April to June 2023, using questionnaires. The collected data were analyzed using the multiple regression method with SPSS 26.0, The results indicated that all three hypotheses were accepted. Financial literacy had a significant positive impact on investment decisions, overconfidence also had a significant positive effect, and herding behavior showed a positive but not significant effect on investment decisions in PT. Phillip Sekuritas Ambon Branch. The study suggests that investors should focus on improving their financial literacy, avoid making decisions based solely on emotions or excessive self-confidence, and strive to be rational in their investment decisions.